Reversible Small‐Molecule Interactions with Coordinatively Unsaturated Metal Centers Held in Metallathiaborane Clusters. Issue 38 (31st July 2017) - Bould, Jonathan; Passarelli, Vincenzo; Oro, Luis A.; Macías, Ramón
Abstract : The metallathiaboranes [8, 8‐(dppe)‐ nido ‐8, 7‐NiSB9 H11 ] [1, dppe = bis(diphenylphosphanyl)ethane], [7‐Et‐8, 8‐(dppe)‐ nido ‐8, 7‐NiSB9 H10 ] (2 ), [9‐Et‐8, 8‐(dppe)‐ nido ‐8, 7‐NiSB9 H10 ] (3 ) and [2, 2‐(dppe)‐ closo ‐2, 1‐NiSB8 H8 ] (4 ) are isolated from the reactions between Cs[ arachno ‐SB9 H12 ], Li[BHEt3 ] and [NiCl2 (dppe)] at low temperature in yields of 30, 1, 0.1 and <1 %, respectively. The arachno ‐nickellathiadecaborane [6, 6‐(dppe)‐ arachno ‐6, 9‐NiSB8 H10 ] (5 ) is isolated from the reaction between [( N, N, N′, N′ ‐tetramethylnaphthalene‐1, 8‐diamine)H][SB8 H11 ], Li[BHEt3 ] and [NiCl2 (dppe)] at low temperature (75 % yield). Compound1 reversibly takes up NH3 in solution, and the characterization of the resulting compound is discussed. Compound5 shows no interactions with ammonia but does reversibly take up CO to give [6, 6, 6‐(CO)(dppe)‐ arachno ‐6, 9‐NiSB8 H10 ] (7 ). The CO molecule is very weakly bound and is lost readily even in the solid state. Similarly to1, the isonido ‐iridathiaundecaboranes [(L)2 ‐H‐ isonido ‐IrSB9 H9 ] (L = PMe3 and PMe2 Ph) also reversibly takes up NH3 to afford [8, 8, 8‐(PMe3 )2 (NH3 )‐ nido ‐8, 7‐IrSB9 H10 ]· NH3 (8 ) and [8, 8, 8‐(PMe2 Ph)2 (NH3 )‐ nido ‐8, 7‐IrSB9 H10 ] (9 ) quantitatively. The ferrathiaborane compound [1, 1, 3‐(dppe)2 ‐1, 2‐ closo ‐FeSB9 H9 ] (11 ) was isolated in trace yield when [FeCl2 (dppe)] was used as the starting metal complex. When appropriate, the compounds were characterized by single‐crystal X‐ray diffraction studies, multielement NMR spectroscopy together with DFT gauge including atomic orbitals (GIAO) chemical‐shielding calculations, IR spectroscopy and elemental analysis. Abstract : The interactions of new metallathiaboranes with the small molecules NH3 and CO are investigated. The reversible uptake of the molecules can be modified by changing the metal, the thiaborane fragment or the ligand sphere. This chemistry represents the first stage in our design of new systems for the activation of small molecules using earth‐abundant metals.